Carbon Isotopic Evidence for Gas Hydrate Release and Its Significance on Seasonal Wetland Methane Emission in the Muli Permafrost of the Qinghai-Tibet Plateau - Xiaoqian Li; Jianwei Xing; Shouji Pang; Youhai Zhu; Shuai Zhang; Rui Xiao; Cheng Lu (International Journal of Environmental Research and Public Health, 2022)
In order to determine the significant role of gas hydrate in seasonal wetland methane emission at the drilling-affected permafrost, the carbon isotopic monthly field monitoring of methane (CH4), as well as carbon dioxide (CO2), emitted from near-surface soil and a gas hydrate drilling well (DK-8) was conducted in the Muli permafrost of the Qinghai-Tibet Plateau. The methane source effused from the well DK-8 was calculated as −25.9 ± 1.4‰ and −26.5 ± 0.5‰, respectively, by the Keeling and Miller Tans plots, with the carbon isotope fractionation (εC) between CO2 and CH4 from −25.3‰ to −32.1‰. The carbon isotopic signatures are indicative of thermogenic origin associated with gas hydrate dissociation. The near-surface soil-emitted methane has δ13CCH4 values between −52.0 ± 1.2‰ and −43.2 ± 1.8‰ with the heaviest in December and the lightest in July. Further, the εC values of near-surface soil-emitted gases were between 28.6‰ and 47.9‰, significantly correlated with the δ13CCH4 values. The linear correlation between εC and δ13CCH4 values indicated binary end-member of microbial and thermogenic sources control the seasonal variation of wetland methane emission. The thermogenically derived methane was identified as the dominant methane source in autumn and winter, compared with the increasing contribution of microbially derived methane in spring and summer. The finding provides reliable evidence for gas hydrate release on the seasonal wetland methane emission in the Muli permafrost affected by drilling activities. The combined application of εC and δ13CCH4 to distinguish thermogenic from biogenic methane is well established and powerful in complex environments, which can provide an improved constraint on source apportionment for wetland emitted methane in the permafrost of the Qinghai-Tibet Plateau.